Synthesis and molecular docking of 2, 4, 5-trisubstituted-1,3-thiazole derivatives as antibacterial agents - Abdullah Ripain, Iswatun Hasanah; Roslan, Norashikin; Norshahimi, Nurul Shazana; Mohamed Salleh, Siti Salwa; Muhamad Bunnori, Noraslinda; Ngah, Nurziana (2018)
The emergence of antibiotic resistance against bacterial strains has attracted great interest in the discovery and development of new antibacterial agents. Thiazole derivatives have been widely used in the biological as well as pharmacological fields and their efficiency as pharmaceutical drugs are well established. In this study, a series of thiazole derivatives were synthesized in reaction between 3-chloroacetyl acetone and ammonium thiocyanate followed by incorporating selected primary amines in one-pot synthesis manner. The compounds were structurally characterized by FTIR, 1H NMR, UV-Vis and GC-MS. Their antibacterial properties were screened using disc diffusion technique against Gram positive (B. cereus and S. epidermidis) as well as Gram negative (E.coli and P. aeruginosa) bacterial strains. The compound of T3 exhibited the most potent antibacterial activity. Molecular docking studies were also performed against Glucosamine-6-phosphate (GlcN-6-P) synthase which is known as the essential building block of most bacteria. According to the docking result, T3 exhibited the minimum binding energy of -7.09 kcal mol-1 as compared to T1 and T2 with -6.49 and 6.76 kcal mol-1,respectively which is in agreement with antibacterial result. The output of this preliminary study will contribute in structural enhancement in drug discovery.